Tantangan Globalisasi Dalam Perspektif Kebudayaan Islam - Mitra Sari; Miranda Miranda; Manda Manda; Muhammad Ramadon; Dwi Noviani (Journal of Innovative and Creativity, 2025)
The widespread development of technology has had an impact on society in the era of globalization on Islamic cultural values, especially referring to morals, behavior, culture, and community habits. This study aims to describe the influence of globalization so that society does not cultivate these negative influences and continues to maintain Islamic cultural values ​​in the era of globalization. The influence of globalization has had a very large impact on Islamic culture, both positive and negative impacts. The positive impact provides ease in exchanging information, broadening horizons, and being an effective means of spreading Islamic values ​​in society. However, the negative impact of globalization also presents its own challenges, such as the emergence of a consumptive lifestyle, behavior that imitates Western nations, the decline of morals and ethics in the current generation, resulting in a decline and shift in Islamic values ​​​​in society, especially among teenagers who are more interested in foreign cultures than their own culture. This study shows that globalization can bring progress in science and technology, but also threatens the morals and values ​​​​of Islamic culture. Therefore, this study emphasizes the need for character formation such as instilling an attitude of nationalism, strengthening faith and morals from an early age. Thus, it is hoped that society can utilize technological advances in this era of globalization without losing its Islamic identity and values.